2012
DOI: 10.1016/j.neuint.2012.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Social memory, amnesia, and autism: Brain oxytocin secretion is regulated by NAD+ metabolites and single nucleotide polymorphisms of CD38

Abstract: Previously, we demonstrated that CD38, a transmembrane protein with ADP-ribosyl cyclase activity, plays a critical role in mouse social behavior by regulating the release of oxytocin (OXT), which is essential for mutual recognition. When CD38 was disrupted, social amnesia was observed in Cd38 knockout mice. The autism spectrum disorders (ASDs), characterized by defects in reciprocal social interaction and communication, occur either sporadically or in a familial pattern. However, the etiology of ASDs remains l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 91 publications
0
62
0
1
Order By: Relevance
“…Individuals with ASD have particular difficulty in interpreting nonverbal social information such as facial expressions, vocal expressions (Doi et al, 2013), pointing gestures (Paparella et al, 2011), and body gestures (Centelles et al, 2012) that lead to severe social impairment (Hill and Frith, 2003). Recently, many studies have revealed relations between OT and social functioning (e.g., Munesue et al, 2010; Higashida et al, 2012), and have devoted particular attention to OT as a candidate treatment for social impairments in patients with ASD. In fact, plasma OT levels in patients with ASDs are reportedly low (Modahl et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with ASD have particular difficulty in interpreting nonverbal social information such as facial expressions, vocal expressions (Doi et al, 2013), pointing gestures (Paparella et al, 2011), and body gestures (Centelles et al, 2012) that lead to severe social impairment (Hill and Frith, 2003). Recently, many studies have revealed relations between OT and social functioning (e.g., Munesue et al, 2010; Higashida et al, 2012), and have devoted particular attention to OT as a candidate treatment for social impairments in patients with ASD. In fact, plasma OT levels in patients with ASDs are reportedly low (Modahl et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, it is clear that CD38 plays pivotal roles under neuronal physiological as well as pathophysiological conditions (Malavasi et al, 2008;Rah et al, 2012;Higashida, et al, 2012aAkimoto et al, 2013). DNA manipulation of CD38 and cADPR in the mAChR-signal cascade in NG108-15 cells revealed that CD38 has great impact on M-current inhibition.…”
Section: Discussionmentioning
confidence: 86%
“…Being actually NAD + -glycohydrolase, CD38 synthesizes cyclic ADP-ribose which is a Ca 2+ -mobilizing second messenger present in OT-producing neurons (Jin et al, 2007). Therefore, researchers have postulated that impaired CD38-mediated OT release might be caused by intracellualar NAD + depletion (i.e., under conditions of oxidative stress or DNA damage and hyperactivation of NAD + -consuming DNA repair enzymes), and diminished CD38 expression or lower enzymatic activity may lead to prominent alterations in various aspects of mammalian social behavior (Jin et al, 2007; Higashida et al, 2012; Lopatina et al, 2012). Low CD38 expression is associated with a risk for ASD through impaired OT secretion (Lerer et al, 2010).…”
Section: Oxytocin and Control Of Face Recognition In (Patho)physiologmentioning
confidence: 99%